A classification of deception in operations and supply chain management: A case study of deception in Australian souvenir markets - Plant, Amy; Hammadi, Adil; Taylor, Ruth; Reiners, Torsten; Wood, Lincoln (2019)
Sustainability concepts inform business considerations of production and procurement in order to satisfy consumer demands for ethical products. Drawing on the Deception Impact Model, the aim is to understand the severity of deception, implementation of socially sustainable practices, and impact on consumers by examining a case in the Indigenous art Australian souvenir industry. It found where a firm decouples from socially sustainable practices the result, a form of deception, negatively impacts ethically motivated consumers. The paper highlights where Indigenous people should be involved in the development chain to avoid infringing on human rights as it relates to commodification of culture.